Pengaruh Penggunaan Pendekatan Contextual Teaching And Learning (Ctl) Terhadap Hasil Belajar IPA Kelas V SDN 13 Cingkariang - Novianti, Suci; Zen, Mulyani; Harni, Harni (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2016)
This study aims to determine the effect of using the Contextual Teaching andLearning (CTL) approach to learning outcomes in Natural Sciences (IPA) in class V of SDN 13 Ciangkariang. This type of research is a quasi-experimentaldesign with a non-equivalent control group design. The population is the fifth grade students of SDN 13 Cingkariang totaling 46 students with class A samples totaling 23 students as the experimental class and class B totaling23 students as the control class. The results of the study obtained an averagepretest value of 46.95, the posttest value of 73.21 for the experimental class and for the control class the pretest value was 56.69 and the posttest value was 64. Based on the t-test calculation (t-test) obtained tcount (2.9323)> t table (1.68023) at a significant level of 0.05. So it can beconcluded that the use of the contextual teaching and learning (CTL) approach affects the learning outcomes of Natural Sciences (IPA) in thefifth grade of SDN 13 Cingkariang. Keywords: CTL Approach, Learning Outcomes, Science